Extinct equids from Limeworks Cave and Cave of Hearths, Makapansgat, Northern Province, and a consideration of variation in the cheek teeth of Equus capensis Broom - Churcher, C S Rufus (Bernard Price Institute for Palaeontological Research, 2000)
Dental specimens of Hipparion libycum from Limeworks Cave, and Equus capensis from Cave of the Horse’s Mandible in the Limeworks Cave entrance and from Cave of Hearths on the farm Makapansgat in the Makapansgat Valley are described. The concept of restricted local formations within each cave is discussed. Qualitative variation in the cheek teeth of E. capensis, based on a sample of 40 upper and 60 lower permanent premolars and molars from Cave of Hearths, demonstrates that there appears to be no correlation in the occurrence of one enamel feature with another between teeth of presumed different individuals. Teeth within a molar row show similar development of features between teeth, whether premolar or molar, as shown by plis, progressive migration of the protocone isthmus along the row, and penetration of the buccal valley to between the enamel loops of the metaconid and metastylid. Consequently, earlier descriptions of species of large Pleistocene Equus in Southern Africa founded on isolated teeth and, using such qualitative variation, are inept, unsuitable and inappropriate, and modem taxonomies synonymising them under E. capensis are supported. The Cave of Hearths ‘loose breccia’ (Beds 1-3 of Mason, 1988) containing earlier Stone Age/Later Acheulean artifacts, is circumstantially dated between 300 000 and 200 000 years BP.
Keywords: Makapansgat Valley; Late Pleistocene; Cave of Hearths; Limeworks Cave; Hipparion lybicum; equus capensis; dental variation